Much to do about identity: Successful women in science reflect on their school years. (30th September 2022) - Hall, Jonathan L.; Butler, Malcolm B.
Abstract: This study presents the recollections of 12 successful women in science during their school years before postsecondary education. The participants shared detailed descriptions of their science experiences through three semi‐structured interviews. An identity works conceptual framework consisting of figured worlds, positioning, and agency constructs to portray the complex dynamics of their experiences was used to analyze the data. The following four themes emerged from the data analysis: participants had an early interest in mathematics and science; they were "stubbornly" persistent in science‐figured worlds; they engaged in science‐figured worlds beyond school; and they positioned themselves as science leaders. These findings add to the evolution of science identity development theoretical models because they are from a nondeficit perspective. Participants engaged in identity work that advanced their science identities despite the gender biases in science‐figured worlds. From a practical stance, girls and women could employ the agentic and positive positioning identity work that the findings show to develop their science identity in educational contexts. Science educators and researchers are encouraged to structure figured worlds where girls feel empowered to enact identity work to build strong science identities.